An Experimental Study Of Unsteady Vortex / Turbulent Boundary Layer Interactions - Haji Serakawi, Abdul Rashid (2011)
The main aim of the present study is to investigate the performance of an oscillating sub boundary layer vortex generator (SBVG) through experimental approach. The current research work will focus on the interaction between turbulent boundary layer and SBVG. The vortex generator height, ℎ is approximately equal to 20% of the boundary layer thickness, . The work is divided into two parts i.e. steady (passive) SBVG and oscillating (active) SBVG. The steady vortex was created by the static SBVG with angle of incidence, of 18° with different vortex generator chord length, height, and spacing between vortex generators. In order to create unsteady vortex, the SBVG was oscillated at a number of frequencies.